Avianbase: a community resource for bird genomics - Eöry, Lél (Genome Biol, 2015)
Giving access to sequence and annotation data for genome assemblies is important because, while facilitating research, it places both assembly and annotation quality under scrutiny, resulting in improvements to both. Therefore we announce Avianbase, a resource for bird genomics, which provides access to data released by the Avian Phylogenomics Consortium.